Effect of melanogenesis inhibition by a yeast extract in comparison to that by other food extracts, and its mechanism of action. Issue 3 (18th February 2018) - Fukunaga, Shoko; Wada, Sayori; Aoi, Wataru; Osada‐Oka, Mayuko; Minamiyama, Yukiko; Ichikawa, Hiroshi; Higashi, Akane
Abstract: Rice, wheat, maize, and konjac extracts are rich in ceramide and used for cosmetic applications. However, the differences in efficacy between ceramides from different sources have not been elucidated. Therefore, we compared the anti‐melanogenesis effects of ceramide‐rich food extracts (yeast, rice, and maize) and purified food‐derived ceramides (from yeast, mushrooms, rice, wheat, and maize). We also investigated the mechanism of the inhibitory effect of yeast extract. The yeast extract suppressed melanogenesis to a greater extent than other food extracts; however, purified rice‐ and maize‐derived ceramides inhibited melanogenesis more than yeast‐derived ceramide. Additionally, ceramide‐free yeast extract suppressed melanogenesis in a dose‐dependent manner. In the melanin synthetic pathway, purified yeast‐derived ceramide attenuated melanogenesis by inhibition of tyrosinase. However, ceramide‐free yeast extract decreased the protein expression of tyrosinase related protein‐1 (TRP1), resulting in inhibition of melanogenesis. These results indicate that ceramides, as well as other unidentified components of yeast extract inhibit melanogenesis. Practical applications: The yeast extract might have two synergistic effects on melanogenesis; tyrosinase inhibition and tyrosinase related protein‐1 inhibition. The safety of yeast extract for human oral administration is already proven, and it can be supplied inexpensively using yeast fermentation systems. These characteristics are advantages of ceramide‐rich yeast extract over the existing ceramide‐rich food extracts. It is also expected that yeast extract could be developed as an effective skin‐whitening agent.